A Qualitative Investigation of Former Clients’ Perception of Change, Reasons for Consultation, Therapeutic Relationship, and Termination - Olivera Ryberg, Julieta María (2013)
The purpose of this research is to investigate former client’s perception of change, reasons for consultation, therapeutic relationship, and termination. Semistructured interviews were conducted with 17 former clients who had been in a psychotherapeutic treatment. A qualitative approach, based on consensual qualitative research (CQR) was used to analyze the interviews. Results show how the balance of negative and positive aspects of the therapeutic relationship is associated with the perception of change. Likewise, categories related to reasons for consultation were associated with types of change and therapy termination. The relevance of the client’s perspective is increasingly being recognized as valuable for the understanding of the psychotherapeutic processes and generates hypotheses for future research.